Calculation of the structure of electrostatic quadrupole-cylindrical fields - Zh.T. Kambarova; А.О. Saulebekov (Қарағанды университетінің хабаршысы. Физика сериясы)
The paper is devoted to the investigation of electrostatic quadrupole-cylindrical fields. Calculation of the structure of electrostatic quadrupole-cylindrical fields, synthesized on the basis of the sum of the base cylindrical field and axially symmetric cylindrical quadrupoles of various types, is carried out. Equipotential portraits of quadrupole-cylindrical fields of various types are presented. The analysis of obtained equipotential portraits of quadrupole-cylindrical fields is carried out. Variants of their application in corpuscular optics are discussed. The addition of components of the axially symmetric cylindrical quadrupole to the base cylindrical field selectively affects corpuscular-optical parameters of the energy analyzer, and variants of the schemes of mirror analyzers with improved quality of angular focusing can be found.